Optimization and Automation of the Nuclear Reaction Chamber - Silva, Manuel Joaquim dos Santos Moreira da (2021)
The production of vacuum is usually a very lengthy process that occupies precious research time. When dealing with many samples, the amount of times vacuum will have to be produced is directly tied to the number of samples a sample holder can take. This problem becomes much more important when dealing with samples that take longer to generate vacuum in the vacuum chamber, such as biological samples. Associated with this work is the construction of a new sample holder capable of holding up to fifteen samples, a new lid associated with the necessities of the new design, the incorporation of a linear feedthrough and a rotary platform, the construction of a new faraday cage to minimize associated noise and coding to automatically alternate between samples in both a linear and angular fashion. This new setup is going to be mounted in the target chamber of the nuclear reactions beam line of the 3.0 MV tandem accelerator located at CTN-IST (Bobadela Campus) and will give the nuclear reactions group new analysis capabilities. The design of the new parts was done with the usage of SolidWorks, and the development of the code was done with the usage of both Python for the user interface and Arduino for the control of the motors motion.